2018
DOI: 10.1186/s12873-018-0173-6
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficiency of a redirection procedure toward an out of hours general practice before admission to an emergency department, an observational study

Abstract: BackgroundPrimary care patients are often cited as a cause of Emergency Department overcrowding (ED). The aim of this study was to evaluate a physician led redirection procedure of selected patients towards an out of hours general practice (OHGP) in an Emergency Department with 55,000 admissions per year.MethodsObservational monocentric study over a period of 2 months. Every patient redirected to the OHGP was included and subsequently contacted by telephone to answer a standardized questionnaire, in order to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Thus, a multi-pronged approach may be required to limit excessive non-urgent visits. For example, simply redirecting non-urgent patients to other settings has been shown not to be wholly effective [ 108 ]. Instead, ensuring health care providers (at both PCP clinics and ED) understand how and why patients make decisions may help to provide insight and direct patient education.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a multi-pronged approach may be required to limit excessive non-urgent visits. For example, simply redirecting non-urgent patients to other settings has been shown not to be wholly effective [ 108 ]. Instead, ensuring health care providers (at both PCP clinics and ED) understand how and why patients make decisions may help to provide insight and direct patient education.…”
Section: Discussionmentioning
confidence: 99%
“…As many as 50 to 88% of low-acuity ED patients initially seek but unsuccessfully access primary care 4 or would prefer a primary care appointment over an ED visit for their nonurgent needs. 5 Moreover, when redirected to alternative settings, ED patients report very high satisfaction rates (> 80%) with their care. 5 Furthermore, an extensive redirection protocol implemented in Montréal in 2015 has been used to date on more than 52,000 patients from five different hospitals.…”
Section: Advancing Patient-centred Carementioning
confidence: 99%
“…5 Moreover, when redirected to alternative settings, ED patients report very high satisfaction rates (> 80%) with their care. 5 Furthermore, an extensive redirection protocol implemented in Montréal in 2015 has been used to date on more than 52,000 patients from five different hospitals. Research on this protocol showed that eligible patients who accepted to be redirected away from the ED were four times more likely to be satisfied with their care than those choosing to stay in the ED after being offered but declining a 24-to 48-hour appointment at a walk-in clinic.…”
Section: Advancing Patient-centred Carementioning
confidence: 99%
See 1 more Smart Citation
“…Other strategies are used to identify redirection eligible patients such as implementing a systematic emergency physician assessment at the ED entrance or selecting them based on their chief complaint. Both strategies have important limits and are not reproducible nor can they be extrapolated to other settings [21,39,40]. A proper identification strategy should take into account various patient information, medical history, vital risk assessment, chief complaint, but also its environment and comprehensiveness of the redirection process.…”
Section: Introductionmentioning
confidence: 99%